2012
DOI: 10.1371/journal.pone.0050353
|View full text |Cite
|
Sign up to set email alerts
|

The Abundance and Pollen Foraging Behaviour of Bumble Bees in Relation to Population Size of Whortleberry (Vaccinium uliginosum)

Abstract: Habitat fragmentation can have severe effects on plant pollinator interactions, for example changing the foraging behaviour of pollinators. To date, the impact of plant population size on pollen collection by pollinators has not yet been investigated. From 2008 to 2010, we monitored nine bumble bee species (Bombus campestris, Bombus hortorum s.l., Bombus hypnorum, Bombus lapidarius, Bombus pascuorum, Bombus pratorum, Bombus soroensis, Bombus terrestris s.l., Bombus vestalis s.l.) on Vaccinium uliginosum (Erica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 57 publications
1
32
0
Order By: Relevance
“…Unlike other Salix species (Füssel 2007 mart 1993;MacKenzie and Eickwort 1996;Javorek et al 2002;Mayer et al 2012) bumblebees were the main visitors of V. myrtillus. Andrena species were also caught on V. myrtillus flowers.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Unlike other Salix species (Füssel 2007 mart 1993;MacKenzie and Eickwort 1996;Javorek et al 2002;Mayer et al 2012) bumblebees were the main visitors of V. myrtillus. Andrena species were also caught on V. myrtillus flowers.…”
Section: Discussionmentioning
confidence: 91%
“…Because of their economic importance, much of the research on habitat use by pollinators has been carried out in agricultural ecosystems (Osborne et al 1999;Persson and Smith 2013); nevertheless, work has also been carried out in semi-natural and natural ecosystems (Lack 1982;Petanidou and Ellis 1993;Carvell 2002;Potts et al 2003). Among semi-natural ecosystems, less attention has been paid to heathland ecosystems (but see Descamps et al 2015;Forup et al 2007;Kaiser-Bunbury et al 2009;Mayer et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It was confirmed that populations which cannot freely move between habitats are forced to inbreed, and this leads to a decrease in the condition of the whole population (Krebs 2009). Habitat fragmentation may cause a situation where too small sites with food plants will not be attractive for some bumblebee species (Mayer et al 2012).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Several hypotheses have been proposed to explain this global decline such as (i) habitat fragmentation (Williams, 1982;Williams & Osborne, 2009;Darvill et al, 2010;Mayer et al, 2012;Hatten et al, 2013), (ii) shortage of flower resources (Peters, 1972;Williams, 1989;Rasmont & Mersch, 1988;Rasmont et al, 1993Goulson et al, 2005Goulson et al, , 2008a, (iii) killing by car traffic (Donath, 1986), (iv) overgrazing of bumblebee habitat by cattle (Özbek, 1995;Xie et al, 2008), (vi) parasites and pathogens resulting from spillover from domesticated species Arbetman et al, 2013), (vii) urbanization (Ahrné et al, 2009;Martins et al, 2013), or (viii) vegetation displacement due to nitrogen deposition (Rasmont, 2008). Pesticides have most likely also played a role because of their extreme toxicity for some bumblebee species (e.g.…”
Section: Contextmentioning
confidence: 99%